Poly(amidoxime) chelating ligand from pine wood cellulose for eco-friendly toxic metals extraction from water sources - Md Lutfor Rahman; Mohd Asyraf Aiman; Mohd Sani Sarjadi; Sazmal Effendi Arshad; Shaheen M. Sarkar; Sandeep Kumar (Elsevier, 2025)
Industrial, domestic, and agricultural activities have significantly contributed to environmental pollution, with heavy metal contamination from wastewater emerging as a critical issue. In this study, nanocellulose was extracted from pine wood and chemically modified via graft copolymerization. Free radicals generated on the cellulose backbone facilitated the grafting of acrylonitrile monomers, resulting in poly(acrylonitrile)-grafted nanocellulose. This intermediate product was further transformed into poly(amidoxime), a chelating polymer ligand specifically designed for heavy metal extraction from aqueous media. Batch adsorption experiments evaluated the removal efficiency of heavy metal ions, including copper (Cu 2+ ), iron (Fe 2+ (Ni 2+ ), and lead (Pb 2+ ). Analytical results revealed that Cu 2+ ), cobalt (Co 2+ ), nickel exhibited the highest adsorption capacity of 335 mg/g at pH 6. Other metal ions also showed significant adsorption capacities, including Fe 2+ (241 mg/g), Ni 2+ (205 mg/g), and Pb 2+ (281 mg/g), Co 2+ (306 mg/g), confirming the polymer’s effectiveness in heavy metal removal. Adsorption behavior was analyzed using the Langmuir isotherm model, which assumes monolayer adsorption on a surface with uniformly distributed active sites. The experimental data aligned well with this model, demonstrating predictable and efficient adsorption performance. Reusability studies indicated that the poly(amidoxime) ligand retained its adsorption capacity over six cycles with minimal degradation, highlighting its sustainability. This suggests its potential as a cost-effective and reusable material for heavy metal remediation. By combining high adsorption capacity with reusability, poly(amidoxime) provides a durable and efficient solution for addressing heavy metal contamination in wastewater, significantly contributing to environmental sustainability through improved water treatment methods.